Muslim women in contemporary societies: realities and opportunities - Ahmed Ibrahim, Hassan; Kamaruddin, Zaleha (2010)
This book brings to focus, ideas articulated by some contemporary Muslim writers during a three-day conference organized by the International Institute for Muslim Unity (IIUM), on the politico-religious and socio-economic challenges of Muslim women in our time. Edited by Hassan Ahmed Ibrahim and Zaleha Kamaruddin, the book which features seventeen essays with an introductory note, addresses the challenges facing Muslim Women across diverse cultural and national backgrounds. With a gist that discrimination against women has no basis in Islam; the authors suggested what should be done in order to remedy the dominant misrepresentation in many Muslim countries where women are held inferior. The progress made by some Muslim countries where women enjoy political rights and are allowed participation in the public domain were highlighted while places and areas where much need to be done were also given due attention. By and large, the book opens a vista on how Muslim women can be empowered such that the Ummah can optimize their contributions to its civilizational development.